(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2023)
Nowadays, people, states and international organizations feel more threatened and insecure, more than in the past, and this has contributed to an increase in need for security and the establishment of a new order and rules through which the world’s problems will be successfully solved. One of the leading countries is the People’s Republic of China, which is taking an increasing share on the global stage and is striving to reduce the dominance and role of the United States and European countries. The rise of China as an economic, security-military and information-technological power has contributed to the shift of the centre of gravity and power from the West to the East, and a lot of opportunities have been created for other Asian countries to find their place and role and be an important subject in the new international structure. With the inclusion of new actors on the international stage, the balance of power changes and new rules of the game are imposed, contrary to the Western countries. The “new managers” are expected to have greater responsibility and influence in reforming the existing international institutions, as well as reducing the factors that cause instability and lead to an anarchic world order. However, due to the different values, interests and goals promoted by the PRC, a number of security implications of an international nature, intensification of geopolitical and geo-economics rivalries, polarization, emergence of new risks and dangers, and increased tension between great powers are expected.